IIT-Indore ranks 23, IISER-Bhopal 40th in NIRF overall table - (:unkn) unknown (Times of India, 2020)
News demonstrate the ranking of School of Planning and Architecture, Bhopal in the ranking list of National Institutional Ranking Framework (NIRF) in the Architectural category.
Keywords: NIRF Ranking 2020-Architecture Institutions-India; Architecutre Institution-NIRF Ranking 2020; Top Architectural Institution-India